2004
DOI: 10.1017/s0265021504006064
|View full text |Cite
|
Sign up to set email alerts
|

Air leakage around endotracheal tube cuffs

Abstract: The Microcuff endotracheal tube with its ultra-thin polyurethane cuff membrane required the lowest sealing pressure to prevent air leakage. These features are potentially of interest for long-term intubated patients and for cuffed endotracheal tubes in children, allowing tracheal sealing at lower cuff pressures implying less damage to the trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 20 publications
0
43
0
7
Order By: Relevance
“…Underinflation of the endotracheal tube cuff is associated with inadequate delivery of prescribed tidal volume and aspiration of secretions. 6,18,23,[28][29][30][31][32][33][34][35][36] Dullenkopf et al 37 reported that a pressure of 19.1 cm H 2 O was required for an adequate seal of an endotracheal tube cuff. After a study of 83 patients who were intubated with an endotracheal tube that provided continuous aspiration of subglottic secretions, Rello et al 6 recommended a minimum pressure of 20 cm H 2 O.…”
Section: Background Importance Of Cuff Pressure Managementmentioning
confidence: 99%
“…Underinflation of the endotracheal tube cuff is associated with inadequate delivery of prescribed tidal volume and aspiration of secretions. 6,18,23,[28][29][30][31][32][33][34][35][36] Dullenkopf et al 37 reported that a pressure of 19.1 cm H 2 O was required for an adequate seal of an endotracheal tube cuff. After a study of 83 patients who were intubated with an endotracheal tube that provided continuous aspiration of subglottic secretions, Rello et al 6 recommended a minimum pressure of 20 cm H 2 O.…”
Section: Background Importance Of Cuff Pressure Managementmentioning
confidence: 99%
“…Initially, it was thought that the material used in the standard polyvinyl ETT cuffs was the cause of the microchannel formation. 32,33 A new cuff made of polyurethane material that has an ultrathin cuff membrane (thickness of 7 m m compared with a thickness of . 50 m m in the conventional HVLP ETT) may prevent the formation of folds within the ETT cuff.…”
Section: Cuff Materials and Shapementioning
confidence: 99%
“…The cuff has the function to ensure the proper pulmonary ventilation without allowing air leakage (3,(6)(7)(8) , and prevent aspiration of oropharyngeal and gastroesophageal contents into the lungs (3,(6)(7)(8)(9)(10) . The pressure in the cuff is harmful to the tracheal mucosa (6,(9)(10)(11) especially when the pressure setting is not appropriate, using extremely safe values (9)(10)(11) . However, the air volume used to inflate the balloon must not generate higher pressure than the tracheal mucosa perfusion, only a "seal" pressure to enclose de air (7,(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%